Factores que afectan la capacidad en WCDMA y su influencia en la planificación de sistemas de tercera generación (2003)
In this paper we use a model that we have developed for CDMA capacity analysis to see how different conditions like propagation model, number of cells and overlapping affect the estimation of CDMA capacity. We will show that the overlapping is not a direct parameter that affect capacity, and there are other factors to consider.